Immigrant integration in Southeast Europe : policy and outcomes in EU Member States and Candidate Countries. - Cos??kun, Laura Elina (Routledge, 2026)
This book presents a comparative analysis of the integration outcomes of immigrants in Southeast Europe, uncovering cross-country differences and ascertaining if they relate to the national integration policy frameworks within the context of the European Union (EU) accession.Applying a multidimensional approach to measure immigrant integration and investigating a broad range of indicators, such as employment, income, social participation, and naturalization, this book reveals that there is a large cross-country variation in immigrant integration outcomes, and some differences in outcomes can indeed be dotted along the EU's borderlines, as gaps between immigrants and non-immigrants are especially large in member states in the region. The findings highlight the struggles EU member states in Southeast Europe face in adjusting to the more dynamic immigration landscape that EU accession brings.This book will be a valuable resource to scholars and students of immigrant integration, migration governance, European studies, and Southeast European studies, as well as those with an interest in EU enlargement and immigration policymaking.
Keywords: Emigration and immigration law -- European Union countries.; Immigrants -- Cultural assimilation -- Balkan Peninsula.; Balkan Peninsula -- Emigration and immigration.; elektronické knihy; electronic books